2018
DOI: 10.1104/pp.18.00912
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of the Thylakoid Lumenal Deg Protease Homologs in Chloroplast Proteostasis

Abstract: ORCID IDs: 0000-0002-7279-0246 (Y.L.); 0000-0001-6202-5826 (Z.A.)Deg proteases are involved in protein quality control in prokaryotes. Of the three Arabidopsis (Arabidopsis thaliana) homologs, Deg1, Deg5, and Deg8, located in the thylakoid lumen, Deg1 forms a homohexamer, whereas Deg5 and Deg8 form a heterocomplex. Both Deg1 and Deg5-Deg8 were shown separately to degrade photosynthetic proteins during photoinhibition. To investigate whether Deg1 and Deg5-Deg8 are redundant, a full set of Arabidopsis Deg knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 55 publications
3
25
0
Order By: Relevance
“…Impaired protein quality control at thylakoid membranes might be alleviated, but not fully compensated, by the upregulation of the membrane-intrinsic FtsH protease by ;45%. In the Arabidopsis deg1 mutant, FtsH proteases were upregulated as well (Butenko et al, 2018). In the wild type, high light conditions could induce the accumulation of misfolded and unassembled proteins through an increased rate of PSII repair and through protein oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Impaired protein quality control at thylakoid membranes might be alleviated, but not fully compensated, by the upregulation of the membrane-intrinsic FtsH protease by ;45%. In the Arabidopsis deg1 mutant, FtsH proteases were upregulated as well (Butenko et al, 2018). In the wild type, high light conditions could induce the accumulation of misfolded and unassembled proteins through an increased rate of PSII repair and through protein oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this observation and the finding that Deg1 interacted with the D2 protein, the authors also suggested a chaperone role for Deg1 in PSII assembly. In the Arabidopsis deg1 knockout mutant, the abundance of all complexes of the photosynthetic light reactions was reduced by 15% to 30% (Butenko et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass spectrometry was performed at the De Botton Protein Profiling institute of the Nancy and Stephen Grand Israel National Center for Personalized Medicine, Weizmann Institute of Science, essentially as recently described (Butenko et al., ). Samples were subjected to in‐solution tryptic digestion using a modified Filter Aided Sample Preparation protocol (FASP).…”
Section: Methodsmentioning
confidence: 99%